SOME ISSUES OF DIAGNOSTICS IN IMMUNE PATHOLOGY - I. A. Tousankina (Медицинская иммунология)
Present lecture contains an author's opinion concerning diagnostic issues in immunopathology, including primary and secondary immune deficiencies, immune-dependent states that are based on immunopathological syndromes. Original formulations are suggested for some key categories of clinical immunology, physical, instrumental and laboratory diagnostics of immune deficiencies and immune-dependent diseases. The results of original long-term observations, as well as data on Sverdlovsk Regional Register of primary immune deficiencies are presented in the work.